2020
DOI: 10.1111/pce.13858
|View full text |Cite
|
Sign up to set email alerts
|

Frost and drought: Effects of extreme weather events on stem carbon dynamics in a Mediterranean beech forest

Abstract: The effects of short‐term extreme events on tree functioning and physiology are still rather elusive. European beech is one of the most sensitive species to late frost and water shortage. We investigated the intra‐annual C dynamics in stems under such conditions. Wood formation and stem CO2 efflux were monitored in a Mediterranean beech forest for 3 years (2015–2017), including a late frost (2016) and a summer drought (2017). The late frost reduced radial growth and, consequently, the amount of carbon fixed in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 82 publications
1
28
0
Order By: Relevance
“…However, trees fully recovered in the following growing season, which indicates high resilience of beech to this stress event (D' Andrea et al, 2020). In contrast, no effect of summer drought was found on the radial growth of beech in the current year (D' Andrea et al, 2020), but it may be evident in the following year (Decuyper et al, 2020).…”
Section: Beech Tree Ring Features Under Climate Change (Extreme Weather Conditions)mentioning
confidence: 93%
See 3 more Smart Citations
“…However, trees fully recovered in the following growing season, which indicates high resilience of beech to this stress event (D' Andrea et al, 2020). In contrast, no effect of summer drought was found on the radial growth of beech in the current year (D' Andrea et al, 2020), but it may be evident in the following year (Decuyper et al, 2020).…”
Section: Beech Tree Ring Features Under Climate Change (Extreme Weather Conditions)mentioning
confidence: 93%
“…Recent studies showed that late spring frost essentially influenced beech foliage and TRW in the current year (D' Andrea et al, 2020;Decuyper et al, 2020;Sanguesa-Barreda et al, 2021). However, trees fully recovered in the following growing season, which indicates high resilience of beech to this stress event (D' Andrea et al, 2020). In contrast, no effect of summer drought was found on the radial growth of beech in the current year (D' Andrea et al, 2020), but it may be evident in the following year (Decuyper et al, 2020).…”
Section: Beech Tree Ring Features Under Climate Change (Extreme Weather Conditions)mentioning
confidence: 96%
See 2 more Smart Citations
“…Natural disturbances have a key role in forest ecosystem dynamics [1], yet global changes in climate and land-uses have intensified disturbances rates in several biomes with important consequences on the ecosystems resilience [2]. Events like droughts and wildfires are becoming widespread phenomena in vast areas of the globe, potentially affecting the ecosystem services they provide [3,4] even in humid biomes with high rainfall rates, such as Amazonia [5][6][7].…”
Section: Introductionmentioning
confidence: 99%